Engaging electricity consumers in low-carbon development process in the People’s Republic of China - Liangzhe Wang (Управление)
The aim of the study is to create a new organisational and economic mechanism for the development of facilities operating on renewable energy sources in the power supply system of the People’s Republic of China. The article analyses the difference in the total installed capacity of wind and solar power plants with their electricity generation in the Chinese energy system. The author consolidated the problems of development of renewable energy facilities that directly affect the low level of efficiency of their use. The main objective of the study is to examine the organisational and economic possibilities of the Chinese policy to involve idle excess capacities of wind and solar generation without additional direct government investments in the energy sector. The relevance of the research topic is confirmed by the wide coverage at the highest political levels of all countries of the concept of low-carbon development. The article discusses the main trends in the development of wind and solar energy in China, and provides numerous tools for leveling the problems associated with connecting renewable energy facilities to the general energy supply system. The author proposes the use of indirect mechanisms of state regulation of consumer demand for “clean” electricity with the active involvement of consumers in the process of transition to rational consumption and production patterns in order to support the lowcarbon development of the People’s Republic of China.